Optimizing Village Economy Through Improved BUMDes Management in Indonesia: Mengoptimalkan Ekonomi Desa Melalui Peningkatan Pengelolaan BUMDes di Indonesia - Bella Ayu Sabrina; Lailul Mursyidah (Academia Open, 2024)
This study examines the management of BUMDes Sedayu Prima Makmur in Kludan Village, Sidoarjo, identifying issues that hinder significant progress. Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation. Analysis revealed that while goal-setting and procedures are well-implemented, poor marketing limits product visibility. Organizational challenges include a lack of management members and insufficient village government knowledge about BUMDes. Despite good guidance and coordination, supervision is weak due to the absence of annual reports and limited village government involvement. The study highlights areas for improvement to enhance BUMDes performance and support village economic development. Highlight: Effective planning is hindered by poor marketing of existing programs. Organizational structure suffers from insufficient management members. Supervision lacks due to absence of annual reports and limited involvement. Keywoard: BUMDes, village economy, management, marketing, organizational challenges